The influence of phytoestrogens on different physiological and pathological processes: An overview - Petrine, Jéssica C. P.; Del Bianco‐Borges, Bruno (Phytotherapy research, 2021)
Functional foods have nutritional properties and organic functions, which are beneficial to health. Certain types of functional food components are so‐called phytoestrogens, non‐steroidal compounds derived from the metabolism of precursors contained in plants, which originate secondary metabotypes known to induce biological responses and by mimicry or modulating the action of endogenous estrogen. These molecules are involved in several physiological and pathological processes related to reproduction, bone remodeling, skin, cardiovascular, nervous, immune systems, and metabolism. This review aimed to present an overview of phytoestrogens regarding their chemical structure, actions, and effects in the organism given several pathologies. Several studies have demonstrated beneficial phytoestrogen actions, such as lipid profile improvement, cognitive function, menopause, oxidative stress, among others. Phytoestrogens effects are not completely elucidated, being necessary future research to understand the exact action mechanisms, whether they are via estrogen receptor or whether other hidden mechanisms produce these effects. Thus, this review makes a general approach to the phytoestrogen actions, beneficial effects, risk and limitations. However, the complexities of biological effects after ingestion of phytoestrogens and the differences in their metabolism and bioavailability indicate that interpretation of either risk or benefits needs to be made with caution.